Decree 0328 of 1958 and Law 975 of 2005: Reflections on changes of peace negotiated in Colombia - Román Rendón, Raúl Fernando (2020)
Amnesties and pardons in Colombia have been used as a means for political resolution to the armed conflict.  The political negotiation strategy of the armed struggle has not been a determining factor to help cessation of hostilities and the protection of human rights.  In 1958, Legislative Decree 0328 was issued in search of the pacification of the country’s southwest region, but later, it had to be extended to cover the entire territory due to the spreading of the effects of armed conflict to the rest of the country; its validity was short-lived and only provided benefits until 1959.  Between the second half of the 20th century and the beginning of the 21st, several amnesties and pardons were signed in Colombia with different organized armed groups.  In 2005, Law 975 is signed, it is known as the Justice and Peace Law (Ley de Justicia y Paz) and was expected to demobilize the paramilitary groups that operated throughout the national territory and bring forth a shift in the way of negotiating peace.   In addition, the appearance of the category of victim, to whom rights were granted, was configured in Law 975.  The truth began to be spoken in parallel to the construction of historical memory.